2015
DOI: 10.1080/15287394.2015.1068650
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Cytotoxicity Testing System of Acetaminophen Using a Microfluidic Device (MFD) in HepG2 Cells

Abstract: A lab-on-a-chip (LOC) is a microfluidic device (MFD) that integrates several lab functions into a single chip of only millimeters in size. LOC provides several advantages, such as low fluidic volumes consumption, faster analysis, compactness, and massive parallelization. These properties enable a microfluidic-based high-throughput drug screening (HTDS) system to acquire cell-based abundant cytotoxicity results depending on linear gradient concentration of drug with only few hundreds of microliters of the drug.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…1). Greater sensitivity is also reported between 2D HepG2 monolayers, and values quoted in literature for HepG2 2D monolayers by both Bort et al (diclofenac) [56] and Ju et al (acetaminophen) [57]; however, some differences in the methodologies used may account for these differences, for instance, the use of a microfluidics devise by Ju et al Interestingly, it can be hypothesised that this increased toxicity in spheroids is due to the direct cell-cell contacts, increased liver-specific functionality and structure of the HepG2 spheroids allowing the hepatotoxins to exert their effects, in comparison to the 2D monolayers, with their limited monolayer planar cell contacts and lack of transporter functionality. Various other studies have also found that 3D hepatic spheroids are greater predictors of hepatotoxicity than 2D monolayers, supporting the results in this study and the hypothesis that culturing hepatic cells as 3D spheroids increases hepatotoxin sensitivity [58][59][60].…”
Section: Discussionsupporting
confidence: 71%
“…1). Greater sensitivity is also reported between 2D HepG2 monolayers, and values quoted in literature for HepG2 2D monolayers by both Bort et al (diclofenac) [56] and Ju et al (acetaminophen) [57]; however, some differences in the methodologies used may account for these differences, for instance, the use of a microfluidics devise by Ju et al Interestingly, it can be hypothesised that this increased toxicity in spheroids is due to the direct cell-cell contacts, increased liver-specific functionality and structure of the HepG2 spheroids allowing the hepatotoxins to exert their effects, in comparison to the 2D monolayers, with their limited monolayer planar cell contacts and lack of transporter functionality. Various other studies have also found that 3D hepatic spheroids are greater predictors of hepatotoxicity than 2D monolayers, supporting the results in this study and the hypothesis that culturing hepatic cells as 3D spheroids increases hepatotoxin sensitivity [58][59][60].…”
Section: Discussionsupporting
confidence: 71%
“…The microfluidic cell culture device was fabricated using a soft lithographic technique [35][36][37][38] to investigate mineralization of SHED by indirectly culturing various oral cells under a mimicked cell microenvironment. This microfludic culture system was designed for continuous perfusion culture and forming a chemical gradient.…”
Section: Fabrication Of the Microfluidic Cell Culture Devicementioning
confidence: 99%
“…Microfluidic HTS systems (typically considered a precursor to OOC systems), where cells are cultured in microfluidic channels, do incorporate flow components in a miniaturized manner (leading to low fluid consumption, assay miniaturization, and parallel processing) [7,8,9,10]. Yet, they cannot assess detailed information regarding the effects of generated metabolites, bioaccumulation, cell-ECM interactions, and processing via organs as it travels throughout the human body.…”
Section: Conventional Environmental Toxicology Screeningmentioning
confidence: 99%